Correlation between specific rubella immunoglobulin G (Ig G) and response evoked brainstem audiometry examination on confirmed congenital rubella syndrome (CRS) patients - Rianto, Bambang Udji Djoko; Pratomo, Akmaluddin Agung; Prasetyo, Ashadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Congenital rubella syndrome (CRS) is a health problem that can cause deaf child. Itsdiagnosis is based on clinical manifestation, specific rubella Immunoglobulin M (IgM) andIgG examination. The aim of this study was to evaluate the correlation between the specificrubella IgG level and the brainstem evoked response audiometry wave V. This was across sectional study involving congenital rubella syndrome (CRS) child patients at Dr.Sardjito General Hospital, Yogyakarta from 2011 to December 2016. The inclusion criteriawere 1) aged less than 24 months; 2) wave V of brainstem evoked response audiometryexamination has been identified. The exclusion criteria were 1) the patient’s parents refusedto participate and 2) incomplete data. Based on α: 5%, β: 20% and coefficient correlationestimation 0.04, minimal sample size were 47 subjects. All of subjects was underwentspecific rubella IgG examination. Statistical analysis by using Spearman`s correlation test.Wave V at the level <25 dB were found in 2 patients (4.3%), 26-40 dB results in 3 (6.4%)patients, 41-60 dB in 1 (2.1%) patient, 61-80dB was found in 9 (19.1%) patients and > 81db in 32 (68.1%) patients. A significant positive linear correlation between IgG levels (4-400 IU/mL) and wave V of brainstem evoked response audiometry was reported (p<0.05;r = 0.432). In conclusion, there is a positive correlation between specific rubella IgG leveland brainstem evoked response audiometry test results.